Rainfall runoff modeling using radial basis function neural network for sungai Tinjar catchment, Miri, Sarawak - Suhaimi, S.; Razali, I. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study is to purposefully develop a rainfall runoff model for Sg. Tinjar with outlet at Long Jegan using Radial Basis Function (RBF) Neural Network. Training and simulation was done using MatLab 6.5.1 software with varying parameters to obtain the optimum result.